Enhancement of red blood cell transfusion compatibility using CRISPR‐mediated erythroblast gene editing - Joseph Hawksworth; Timothy J Satchwell; Marjolein Meinders; Deborah E Daniels; Fiona Regan; Nicole M Thornton; Marieangela C Wilson; Johannes GG Dobbe; Geert J Streekstra; Kongtana Trakarnsanga; Kate J Heesom; David J Anstee; et al. (EMBO Molecular Medicine, 2018)
Abstract Regular blood transfusion is the cornerstone of care for patients with red blood cell (RBC) disorders such as thalassaemia or sickle‐cell disease. With repeated transfusion, alloimmunisation often occurs due to incompatibility at the level of minor blood group antigens. We use CRISPR‐mediated genome editing of an immortalised human erythroblast cell line (BEL‐A) to generate multiple enucleation competent cell lines deficient in individual blood groups. Edits are combined to generate a single cell line deficient in multiple antigens responsible for the most common transfusion incompatibilities: ABO (Bombay phenotype), Rh (Rhnull), Kell (K0), Duffy (Fynull), GPB (S−s−U−). These cells can be differentiated to generate deformable reticulocytes, illustrating the capacity for coexistence of multiple rare blood group antigen null phenotypes. This study provides the first proof‐of‐principle demonstration of combinatorial CRISPR‐mediated blood group gene editing to generate customisable or multi‐compatible RBCs for diagnostic reagents or recipients with complicated matching requirements.